Description of a newly discovered Triatoma infestans (Hemiptera: Reduviidae) Foci in Ibipeba, State of Bahia, Brazil - Araújo, Renato Freitas (2014)
Introduction Chagas disease transmitted by the Triatoma infestans was eradicated from Brazil in 2006. However, reports of triatomine foci threaten the control of Chagas disease. The goal of this study was to determine T. infestans foci in the City of Ibipeba, State of Bahia.Methods Triatominae specimens were collected in Ibipeba and entomologic indicators were calculated using indices of domiciliary infestation, density, and colonization.Results T. infestans foci was discovery in Ibipeba, State of Bahia. Approximately 95% of the specimens were discovered inside dwellings, of which 34% were T. infestans. This species was also discovered forming a colony in tree bark in the peridomicile.Conclusions Triatoma infestans foci in peridomestic ecotopes in Ibipeba, BA, indicate increased the risk of transmission Chagas disease.